Energy and Exergy Analysis of Conventional Automobile Engines: Evaluation of Waste Heat Recovery Potential to Drive Parasitic Loads - Muhammad Ishaq Khan; Lorenzo Maccioni; Franco Concli (Energies)
Road transport plays a significant role in the economic growth of a country. Conventional internal combustion engines (ICEs) are widely used in automobiles, with an efficiency range of 25% to 35%, while the remaining energy is lost through cooling and exhaust gases. Additionally, two parasitic loads—the alternator and the air conditioning (AC) compressor—are driven by the ICE via a belt, further reducing efficiency. In this paper, energy and exergy analysis of the waste heat of exhaust gases has been performed for automobiles equipped with ICEs, i.e., R06A, F8B, K10B, 2NZ-FE, and 2ZR-FE, to evaluate their potential to drive these parasitic loads. The working cycles of these ICE models were simulated using a zero-dimensional MATLAB model based on fundamental governing equations. The results indicate that approximately 10–40 kW of energy is lost through exhaust gases under varying operating conditions for the examined ICEs. The average exhaust gas temperature and mass flow rate for these ICEs are approximately 900 K and 0.016 kg/s, respectively. Based on these findings, an E-turbine retrofit system is proposed to operate under these conditions, recovering exhaust energy to power the alternator and AC compressor. The results showed that the E-turbine generated 6.8 kW of mechanical power, which was converted into 4 kW of electrical power by the generator. This electrical power was used to supply the parasitic loads, thereby enhancing the overall efficiency of ICE.